Effect Of Density To Decrease Bioijuk Heavy Metal Pb Contained On The Water From The River Sail - Jessica Anastasia Sitorus; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThe Sail River is one of the Siak watersheds contaminated with heavy metals Pb. This study aims to determine the decrease in heavy metals Pb in water due to the use of different bioijuk densities. The study was conducted in March-April 2019. This study used a completely randomized design (CRD), with 3 different bioijuk density treatments, namely P1 (rare density), P2 (medium density) and P3 (density of meetings), with 3 replications. The sampling location is carried out in the inlet and outlet area. The results showed that the highest average decrease in Pb heavy metal content was in P3 (0.077 mg / L) with a decrease in effectiveness (EP) of 77%. The treatment of different bioijuk densities did not have a significant effect in decreasing heavy metal levels in the water of the Sail River.Keywords :Bioijuk, Pb, Cd, Bacteria, Effectiveness of decline